2015
DOI: 10.1002/anie.201503141
|View full text |Cite
|
Sign up to set email alerts
|

Pim Kinase Inhibitors Evaluated with a Single‐Molecule Engineered Nanopore Sensor

Abstract: Protein kinases are critical therapeutic targets. Pim kinases are implicated in several leukaemias and cancers. Here, we exploit a protein nanopore sensor for Pim kinases that bears a pseudosubstrate peptide attached by an enhanced engineering approach. Analyte binding to the sensor peptide is measured through observation of the modulation of ionic current through a single nanopore. We observed synergistic binding of MgATP and kinase to the sensor, which was used to develop a superior method to evaluate Pim ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…The confined nanopore interface effectively captures a single molecule from the bulk solution at an applied potential, resulting in the typical ionic blockages for each analyte. Although previous nanopore studies evaluate the phosphorylation of the peptides, it requires genetic engineering of the peptides into the biological nanopores and/or chemical modification of the leading DNA sequence on the model peptides [3437]. Moreover, the previous nanopore sensing interface (e.g., α -hemolysin) exhibits less sensitivity for directly identifying the phosphorylation states of oligonucleotides through the reading of ionic current.…”
Section: Introductionmentioning
confidence: 99%
“…The confined nanopore interface effectively captures a single molecule from the bulk solution at an applied potential, resulting in the typical ionic blockages for each analyte. Although previous nanopore studies evaluate the phosphorylation of the peptides, it requires genetic engineering of the peptides into the biological nanopores and/or chemical modification of the leading DNA sequence on the model peptides [3437]. Moreover, the previous nanopore sensing interface (e.g., α -hemolysin) exhibits less sensitivity for directly identifying the phosphorylation states of oligonucleotides through the reading of ionic current.…”
Section: Introductionmentioning
confidence: 99%
“…This nanopore sensor could be used to detect different Pim kinases such as Pim‐1, Pim‐2, Pim‐3 and cAMP‐dependent protein kinase. By changing Pimtide to a pseudosubstrate peptide, the authors observed synergistic binding of MgATP and Pim kinase to the sensor, which was used to develop a superior label‐free method to evaluate Pim kinase inhibitors . Another example is a hybrid nanopore created by Maglia and co‐workers comprised of αHL‐GroES and single‐ring variant of GroEL .…”
Section: Measuring Enzymatic Activities With Nanopore‐enzyme Hybridsmentioning
confidence: 99%
“…By changing Pimtide to a pseudosubstrate peptide, the authors observed synergistic binding of MgATP and Pim kinase to the sensor, which was used to develop a superior label-free method to evaluate Pim kinase inhibitors. [29] Another example is a hybrid nanopore created by Maglia and co-workers comprised of αHL-GroES and single-ring variant of GroEL. [30] They engineered αHL to function as GroES, a protein that, in complex with GroEL, forms a two- provided explanations for the complicated current patterns, but the exact mechanism for the formation of each current step remains to be elucidated.…”
Section: Construction Of Nanopore-enzyme Hybrid For Monitoring Enzymamentioning
confidence: 99%
“…Due to an early available crystal structure [29], the alpha-hemolysin (αHL) nanopore has been widely engineered over the last twenty years by the Bayley group. The rigidity of its β-barrel made αHL particularly amenable to mutagenesis [30, 31], chemical engineering [32] and rational design of binding elements [33]. Later, other β-barrel pores, such as MspA [34], OmpG [35], aerolysin [36] and FhuA [37] were also characterized by single-molecule electrophysiology.…”
Section: Nanoporesmentioning
confidence: 99%